Spoken dialogue systems technology and design - Minker, Wolfgang (Springer New York, 2011)
Spoken Dialogue Systems Technology and Design covers all key topics in spoken language dialogue interaction, through perspectives from a variety of leading researchers. This volume brings together valuable information in the areas of spoken dialogue analysis, processing emotions in dialogue, multimodality, as well as resources and evaluation. The book also highlights comprehensive information from the field of spoken dialogue systems research and evaluation . Spoken Dialogue Systems Technology and Design is based on a selected subset of papers from the International Workshop on Spoken Dialogue Systems Technology (IWSDS) held at Kloster Irsee, Germany in 2009. There, the latest formal, corpus-based, implementational and analytical work on spoken dialogue systems technology were discussed among researchers and developers in the area from both industry and academia. The IWSDS workshop provides, since 1999, a regular forum for the presentation of research in the discourse and dialogue area to both the larger Spoken Dialogue Systems community, as well as to researchers outside this community.